IRE Students' Perception of The Relevance of IRE Learning In Higher Education: A Qualitative Study In An Academic Environment - Nurul Azizah; Fadli Fadli; Jaya Gusnanda; Fitri Khairunisa; Fauziah Ahmad; Nadya Ranialini (Action Research Journal Indonesia (ARJI), 2025)
The evolving times and increasing complexity of student life demand that Islamic Religious Education (IRE) in higher education be more relevant and contextually grounded. However, a gap still exists between the content of IRE instruction and the actual needs of students in addressing contemporary social, moral, and technological challenges within the academic environment. This study aims to explore the perceptions of students in the Islamic Religious Education program at Raden Intan State Islamic University, Lampung, regarding the relevance of IRE in higher education. Employing a qualitative descriptive approach, data were collected through semi-structured interviews with ten students from diverse academic backgrounds and class levels. Participants were selected using a snowball sampling technique, and the data were analyzed through stages of data collection, reduction, presentation, and conclusion drawing. The findings reveal varied student perceptions of IRE learning. Some students view it as still relevant due to its role in character building, moral and spiritual value formation, and equipping them for campus life challenges. However, others criticized the overly theoretical nature of the instruction, the lack of practical application, and its limited alignment with current social and technological realities. Lecturers who can contextualize material and apply interactive teaching methods are perceived as more effective. The study highlights the need to renew IRE teaching strategies to make them more contextual, responsive to contemporary developments, and centered on active student engagement. It recommends the development of participatory learning strategies, the integration of technology, and the strengthening of theory-practice connections to enhance the internalization of religious values in students' academic and social lives.